Kecerdasan Buatan dan Fatwa Ijma: Perspektif Islam Terhadap Inovasi Modern - Muji, Muji; Khairunnisa, Salsabila (Universitas Islam Internasional Darullughah Wadda'wah, 2024)
Artificial intelligence (AI) is one of the technological innovations that is rapidly developing in various sectors of life. However, its use in modern society raises various questions regarding its suitability with religious principles, especially in the context of Islam. The background of this study is the need to examine the acceptance and fatwas of scholars regarding the use of AI, as well as the impact of its application on the social and moral life of Muslims. This study aims to analyze the Islamic perspective on AI by referring to the principle of ijma' of scholars, and to determine whether this technology is acceptable within the framework of sharia. The research method used is a qualitative approach with literature analysis from various fiqh sources, including tafsir, hadith, and fatwas of contemporary scholars, to explore how AI can be accepted in Islamic law. The results of the study show that, based on the principle of ijma' of scholars, AI that does not conflict with basic Islamic values ​​and does not cause harm can be accepted, although it still requires supervision in its implementation to ensure compliance with sharia. The contribution of this research is to provide insight for policy makers, academics, and the general public about the Islamic view on technological innovation, as well as providing a clearer legal basis for implementing AI technology in everyday life in accordance with sharia principles.